Effects of Red Clover Isoflavones on Growth Performance, Immune Function, and Cecal Microflora of Mice - Rongrong Guo; Xuqin Song; Xiaodie Li; Cheng Zeng; Ying Chen; Chunjie Li; Jian Yang; Deyuan Ou (Animals)
Isoflavone components extracted from red clover have anti-inflammatory, antioxidant and immune boosting effects. We hypothesize that red clover isoflavones (RCIs) achieve health-promoting effects via altering the gut microbiota. A total of 48 mice (20 ± 2 g) were randomly divided into a control group, low-dose group (0.05% RCIs in feed), middle-dose group (0.1% RCIs in feed), and high-dose group (0.2% RCIs in feed) with 12 mice per group. The feeding period was 20 d. The results showed that RCIs can increase the daily gain and decrease the ratio of feed to gain in mice. The organ indexes and blood biochemical indexes of the mice in each RCI group were in the normal range, indicating that RCIs do not damage liver or kidney function. RCI supplementation increased serum immunity and altered the microbial community structure in the cecum of the mice. RCIs can increase the diversity of beneficial bacteria such as Bacteroidaceae, Muribaculaceae, and Akkermansiaceae, and reduced the pathogenic Staphylococcaceae. Therefore, supplementing the diet with RCIs results in improved growth performance and notable alterations in the cecal microbiota in mice, and has potential applications as a feed additive to improve livestock production.